A Human-assistive Robotic Platform with Quadrupedal Locomotion - Shen, Tao (IEEE Int Conf Rehabil Robot, 2019)
Mobility impairment is becoming a challenging issue around the world with a rapid increase on aging population. Existing tools of walking assistance for mobility-impaired people include passive canes or wheeled rollators which increase energy consumption on the users and disturb the users’ walking rhythm, and powered wheeled chairs which could preclude the muscle activities and accelerate the degeneration of the lower limbs. The research in this paper aiming at helping mobility-impaired people proposes a novel robotic platform with quadrupedal locomotion. With motorized actuation, the quadruped robotic platform could accompany the user at the center and provide protection and possible walking assistance if needed. As the robotic platform is equipped with a leg locomotion, it can enlarge the user’s activity environments, such as both indoor flat floor and outdoor uneven terrain. It can even assist the user to involve in some mobility challenging activities, such as climbing stairs. In this paper, we illustrate the mechanical design of the robotic platform. A continuous gait planning is proposed to create a smooth locomotion for the robot. To quantify the performance, a system-level walking experimentation was conducted, and the results showed that quadruped robotic platform can maintain a statically stability which demonstrate the feasibility and capability of the robotic application for walking assistance.